2018
DOI: 10.14709/barbj.11.1.2018.05
|View full text |Cite
|
Sign up to set email alerts
|

Bat activity in the interior of Arabuko-Sokoke Forest and adjacent farmlands in Kenya

Abstract: Although the coastal forests in Kenya are highly threatened by human activities, limited bat research has been undertaken in them or the human-modified habitats around them. We investigated insectivorous bat activity in Arabuko-Sokoke Forest (ASF) and adjacent farmlands, in order to understand how each habitat was used by bats. Bat activity was sampled with Pettersson D240X ultrasound detectors at 69 stations in different vegetation types in ASF (Cynometra forest, Brachystegia woodland and mixed forest) and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…The ASF is a legally protected area, characterised by indigenous vegetation typical of the east African coastal forests [10,17] , while the farmland habitat is completely disturbed and modified into an agricultural landscape. Because the two contrasting habitats had been shown to host various types of insectivorous bat species [9,10] , there was need to provide data on diversity and abundance of invertebrates, which are the primary food items eaten by these bats. The results of our study indicated that the farmland in the eastern part of ASF as well as the interior of ASF and had similar invertebrate abundance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The ASF is a legally protected area, characterised by indigenous vegetation typical of the east African coastal forests [10,17] , while the farmland habitat is completely disturbed and modified into an agricultural landscape. Because the two contrasting habitats had been shown to host various types of insectivorous bat species [9,10] , there was need to provide data on diversity and abundance of invertebrates, which are the primary food items eaten by these bats. The results of our study indicated that the farmland in the eastern part of ASF as well as the interior of ASF and had similar invertebrate abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, many individuals of the order Dipterans, Lepidopteran, and Blattodea were more common in ASF than in the farmland. Therefore, though the interior of ASF has been shown to have low insectivorous bats abundance and activity than the farmland [9][10][11] , most of the invertebrate orders preyed by these bats were also common in the forest interior. This probably indicates that the farmland and the interior of ASF were suitable foraging habitats for the insectivorous bat species found in the two study sites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations